2013
DOI: 10.1007/s00277-013-1920-0
|View full text |Cite
|
Sign up to set email alerts
|

A highly specific q-RT-PCR assay to address the relevance of the JAK2WT and JAK2V617F expression levels and control genes in Ph-negative myeloproliferative neoplasms

Abstract: In Ph− myeloproliferative neoplasms, the quantification of the JAK2V617F transcripts may provide some advantages over the DNA allele burden determination. We developed a q-RT-PCR to assess the JAK2WT and JAK2V617F mRNA expression in 105 cases (23 donors, 13 secondary polycythemia, 22 polycythemia vera (PV), 38 essential thrombocythemia (ET), and 9 primary myelofibrosis (PMF)). Compared with the standard allele-specific oligonucleotide (ASO)-PCR technique, our assay showed a 100 % concordance rate detecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…JAK2V617F mutation would have an influence on blood parameters in MPN, and in ET patients, PLT was lower in JAK2V617F mutated patients [9], conversely, RBC counts and WBC counts were much higher in JAK2V617F positive patients based on Chinese population [11], which was similar to our findings. Moreover, JAK2V617F mutation allele burden might be corrected with the change of the degrees of blood parameters, and in PV patients, a negative statistically significant correlation between the JAK2V617F mutation allele burden and PLT count was observed [26] and no statistically significant correlation was found in the study performed by Edahiro et al [27], in addition, JAK2V617F allele burden was correlated with WBC counts and RBC counts in PV patients based on Chinese population [11]. However, the present data indicated that PLT was positively correlated with JAK2V617F mutation allele burden in PV patients, suggesting that the relationship between blood parameters and JAK2V617F mutation allele burden remained inconsistent.…”
Section: Discussionmentioning
confidence: 98%
“…JAK2V617F mutation would have an influence on blood parameters in MPN, and in ET patients, PLT was lower in JAK2V617F mutated patients [9], conversely, RBC counts and WBC counts were much higher in JAK2V617F positive patients based on Chinese population [11], which was similar to our findings. Moreover, JAK2V617F mutation allele burden might be corrected with the change of the degrees of blood parameters, and in PV patients, a negative statistically significant correlation between the JAK2V617F mutation allele burden and PLT count was observed [26] and no statistically significant correlation was found in the study performed by Edahiro et al [27], in addition, JAK2V617F allele burden was correlated with WBC counts and RBC counts in PV patients based on Chinese population [11]. However, the present data indicated that PLT was positively correlated with JAK2V617F mutation allele burden in PV patients, suggesting that the relationship between blood parameters and JAK2V617F mutation allele burden remained inconsistent.…”
Section: Discussionmentioning
confidence: 98%
“…To date, there are only a few reports comparing mutational analysis at DNA and RNA/cDNA level in hematological neoplasms. A discrepancy has been reported regarding the JAK2 V617F mutation in patients with essential thrombocythemia and polycythemia vera, and also regarding the type A mutation of NPM1 in acute myeloid leukemia (AML) [ 20 , 21 , 22 ]. All reports found significantly higher mutation levels at RNA/cDNA level compared to DNA-level highlighting the potential superior sensitivity of RNA-based assays and the possible impact of this discrepancy on disease phenotype and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While Beillard et al [ 24 ] recommended ABL1 as control gene for RQ-PCR-based diagnosis and MRD detection in leukemic patients because of more stable, uniform expression and lack of pseudogenes, GUSB transcript levels were later confirmed as a suitable alternative [ 25 ]. Other authors described the suitability of ABL1 , BCR and GUSB for BCR-ABL1 quantification [ 15 ] or even considered beta-glucoronidase ( GUSB ) as the most suitable genes tested [ 26 ] because the expression pattern of beta-glucoronidase ( GUSB ) was found more homogenous than that of ABL1 or β2 microglobulin ( B2M ) [ 27 ]. Not to be neglected the main practical advantage of the use GUSB over ABL 1 as housekeeping genes is the performance of BCR-ABL1 and GUSB quantification in one single well (duplex PCR) avoiding the bias introduced by setting-up two spatially distinct TM qPCR reactions.…”
Section: Discussionmentioning
confidence: 99%